2003
DOI: 10.1002/cii.69
|View full text |Cite
|
Sign up to set email alerts
|

How we do it: using a surgical navigation system in the management of the ossified cochlea

Abstract: The ossified cochlea poses both concerns and challenges to any implant team. One of the surgical aims is to implant as many of an implant system's electrodes into the cochlea as close to the modiolus as possible, thus facilitating stimulation of the surviving cell bodies in the spiral ganglion. Within the field of otorhinolaryngology various surgical navigation systems have been introduced to facilitate surgical orientation during endoscopic sinus and skull-base surgery. The principle behind such systems is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…Using intraoperative anatomic landmarks in combination with fiducials, they found the accuracy within the temporal bone region to be between 0.9 to 1.5 mm and found the system decreased operating time and increased safety in a series of 11 patients. The LandmarX system has also been reported to be very effective in one case of split cochlear implant electrode placement 19. Various studies in cadavers of similar infrared emitting diode, optical tracking systems have found excellent accuracies (<1 mm), although these measures do not account for registration errors, preoperative imaging error, or fiducial placement errors 20–22.…”
Section: Discussionmentioning
confidence: 99%
“…Using intraoperative anatomic landmarks in combination with fiducials, they found the accuracy within the temporal bone region to be between 0.9 to 1.5 mm and found the system decreased operating time and increased safety in a series of 11 patients. The LandmarX system has also been reported to be very effective in one case of split cochlear implant electrode placement 19. Various studies in cadavers of similar infrared emitting diode, optical tracking systems have found excellent accuracies (<1 mm), although these measures do not account for registration errors, preoperative imaging error, or fiducial placement errors 20–22.…”
Section: Discussionmentioning
confidence: 99%
“…CAN with the Digipointeur has already been tested in an experimental study simulating cochlear implant surgery with a keyhole approach in five temporal bones [14]. Other studies employed CAN in the case of ossified cochlea during a cochlear implantation [15] or in aural atresia [16]. The procedure should be reproducible and reliable, in order to have confidence with this system.…”
Section: Discussionmentioning
confidence: 98%
“…Because navigation only requires a fixed anatomic target, its application outside the realm of neurological surgery has been proven (especially) for orthopedic surgery (8)(9)(10)(11)(12), but also for otic surgery (13,14), adrenal surgery (15), and liver targeted procedures from concept (16)(17)(18) to reality (19). For oncologic surgery of the rectum, and with the recent evolution of transanal total mesorectal excision (taTME) (20)(21)(22), navigation has been successfully applied to help guide surgeons in real-time with this new and advanced procedure that mandates considerable skill (23,24).…”
Section: Introductionmentioning
confidence: 99%